Diet as therapeutic intervention in Crohn’s disease - Martyna Więcek; Paulina Panufnik; Karolina Pomorska; Konrad Lewandowski; Grażyna Rydzewska (Gastroenterology Review)
Diet plays an important role in the pathogenesis of inflammatory bowel disease. It has an impact on microbiome, host barrier, and immune response. Clinical studies indicate that various dietary interventions such as exclusive enteral nutrition and exclusion diets might be useful for induction of remission in mild to moderate Crohn’s disease, but also for patients failing biological therapy. Current treatment strategies try to solve the problem of poor patient compliance due to the required strict dietary regime. The number of adverse events associated with the use of dietary alternatives is incomparable with the side effects of glucocorticosteroids or biological treatment, which makes them a tempting therapeutic option.